Shared-storage layout for redesigning the damaged-goods warehouse - Yudi Sukmono; Taufiq Qurrahman; Farida Djumiati Sitania (Journal Industrial Servicess, 2022)
The Faculty of Engineering, Mulawarman University's equipment warehouse is divided into the office-stationery warehouse and the damaged-goods warehouse. Office-stationery warehouse stores office stationery, spare parts, and consumables. Meanwhile, the warehouse for damaged goods stores various damaged goods such as furniture, Personal Computer (PC) components, electronic goods, and laboratory equipment. The problem with the warehouse is that many items need to be better organized so they cannot be classified between furniture items, PC components, electronics, and laboratory equipment. Then another problem is the difficulty in collecting inventory data at the Faculty of Engineering, Mulawarman University. Therefore, this study proposes improvements to the warehouse’s layout that is more efficient in storing goods in the damaged-goods warehouse. The method used in this study is shared storage, where fast-moving goods are stored in a storage area near the entrance and exit. The results from the shared storage method show that the damaged warehouse layout of the Faculty of Engineering, Mulawarman University, could be more optimal, causing ineffectiveness of the movement of goods that occurred in the warehouse was unorganized. The proposed redesign of the warehouse layout shows it is better than the layout. It can be seen from the placement of goods according to their classification and the effective distance between the storage area to the door.